Propolis: a natural compound with potential as an adjuvant in cancer therapy - a review of signaling pathways - Valivand, Nassim; Aravand, Sara; Lotfi, Hajie; Esfahani, Azam Janati; Ahmadpour-Yazdi, Hossein; Gheibi, Nematollah (Molecular biology reports, 2024)
Propolis is a natural product used in cancer treatment, which is produced by bees via different sources. The chemical composition of Propolis is determined based on the climatic and geographical conditions, as well as harvesting time and method. This compound has been the subject of numerous investigational endeavors due to its expansive therapeutic capacity which includes antibacterial, anti-fungal, anti-inflammatory, anti-oxidant, anti-viral, and anti-cancer effects. The growing incidence rate of different cancers necessitates the need for developing novel preventive and therapeutic strategies. Chemotherapy, radiotherapy, and stem cell therapy have proved effective in cancer treatment, regardless of the adverse events associated with these modalities. Clinical application of natural compounds such as Propolis may confer promise as an adjuvant therapeutic intervention, particularly in certain subpopulations of patients that develop adverse events associated with anticancer regimens. The diverse biologically active compounds of propolis are believed to confer anti-cancer potential by modulation of critical signaling cascades such as caffeic acid phenethyl ester, Galangin, Artepillin C, Chrysin, Quercetin, Caffeic acid, Nymphaeols A and C, Frondoside A, Genistein, p-coumaric acid, and Propolin C. This review article aims to deliver a mechanistic account of anti-cancer effects of propolis and its components. Propolis can prevent angiogenesis by downregulating pathways involving Jun-N terminal kinase, ERK1/2, Akt and NF-ƘB, while counteracting metastatic progression of cancer by inhibiting Wtn2 and FAK, and MAPK and PI3K/AKT signaling pathways. Moreover, propolis or its main components show regulatory effects on cyclin D, CDK2/4/6, and their inhibitors. Additionally, propolis-induced up-regulation of p21 and p27 may result in cell cycle arrest at G2/M or G0/G1. The broad anti-apoptotic effects of propolis are mediated through upregulation of TRAIL, Bax, p53, and downregulation of the ERK1/2 signaling pathway. Considering the growing body of evidence regarding different anti-cancers effects of propolis and its active components, this natural compound could be considered an effective adjuvant therapy aimed at reducing related side effects associated with chemotherapy and radiotherapy.